Caffeine Restores Neuronal Damage and Inflammatory Response in a Model of Intraventricular Hemorrhage of the Preterm Newborn - Alves-Martinez, Pilar; Atienza-Navarro, Isabel; Vargas-Soria, Maria; Carranza-Naval, Maria Jose; Infante-Garcia, Carmen; Benavente-Fernandez, Isabel; Del Marco, Angel; Lubian-Lopez, Simon; Garcia-Alloza, Monica (Frontiers in Cell and Developmental Biology, 2022)
Germinal matrix-intraventricular hemorrhage (GM-IVH) is the most frequent intracranial hemorrhage in the preterm infant (PT). Long-term GM-IVH-associated sequelae include cerebral palsy, sensory and motor impairment, learning disabilities, or neuropsychiatric disorders. The societal and health burden associated with GM-IVH is worsened by the fact that there is no successful treatment to limit or reduce brain damage and neurodevelopment disabilities. Caffeine (Caf) is a methylxanthine that binds to adenosine receptors, regularly used to treat the apnea of prematurity. While previous studies support the beneficial effects at the brain level of Caf in PT, there are no studies that specifically focus on the role of Caf in GM-IVH. Therefore, to further understand the role of Caf in GM-IVH, we have analyzed two doses of Caf (10 and 20 mg/kg) in a murine model of the disease. We have analyzed the short (P14) and long (P70) effects of the treatment on brain atrophy and neuron wellbeing, including density, curvature, and phospho-tau/total tau ratio. We have analyzed proliferation and neurogenesis, as well as microglia and hemorrhage burdens. We have also assessed the long-term effects of Caf treatment at cognitive level. To induce GM-IVH, we have administered intraventricular collagenase to P7 CD1 mice and have analyzed these animals in the short (P14) and long (P70) term. Caf showed a general neuroprotective effect in our model of GM-IVH of the PT. In our study, Caf administration diminishes brain atrophy and ventricle enlargement. Likewise, Caf limits neuronal damage, including neurite curvature and tau phosphorylation. It also contributes to maintaining neurogenesis in the subventricular zone, a neurogenic niche that is severely affected after GM-IVH. Furthermore, Caf ameliorates small vessel bleeding and inflammation in both the cortex and the subventricular zone. Observed mitigation of brain pathological features commonly associated with GM-IVH also results in a significant improvement of learning and memory abilities in the long term. Altogether, our data support the promising effects of Caf to reduce central nervous system complications associated with GM-IVH.